An Analysis of The Nurses Service In Preventing Stunting at UPT Puskesmas Astana Anyar Bandung - Afrizal Hendra; Ma'ruf Akbar; Rd. Tuty Sariwulan (IJHCM (International Journal of Human Capital Management), 2020)
This study focuses on the nurses’ service in preventing stunting at UPT Puskesmas Astana Anyar, Bandung. This study employs qualitative research method with a phenomenological approach. Data collection was carried out using the informant's perspective (emic perspective), and key instruments, such as observation, interviews, documentation studies, and questionnaires. Qualitative analysis is deployed as the data analysis in this study. The validity of the research findings was measured using the validity and reliability standards of qualitative research, namely: credibility, dependability, confirmability, and transferability. The findings showed that: nurses' service in preventing stunting at UPT Puskesmas Astana Anyar Bandung is considered as quite good; this can be seen from the perceptions and expectations of patients using and receiving the service of stunting prevention.